BETWEEN HEAVEN AND EARTH. RELATIONS BETWEEN A HUMAN BEING AND THEIR SPACE AS A PSYCHOLOGICAL ELEMENT OF BOLESŁAW PRUS’ DEALINGS WITH CONTEMPORANEITY - Jauksz, Marcin (Porównania, 2012)
The article aims at presenting a pivotal moment in shaping of the identity of Ignacy Rzecki, one of the main characters of Bolesław Prus’s Lalka (The Doll). In reference to the character’s background the author of the article proves that the participation in the Hungarian campaign of the year 1848 showed the difference between the ideal and the reality and gave Rzecki an important ability of correctly judging subsequent events. His war experience makes him a skilful participant of Warsaw life in the late seventies and a porte parole to the author, both of whom being artists who aim at directing other people’s attention onto issues and aspect of their interest.